A hybrid 1D/2D coating strategy with MXene and CNT towards the interfacial reinforcement of carbon fiber/poly(ether ether ketone) composite. (November 2022) - Xu, Nuo; Chen, Shaohua; Li, Yingze; Jiang, Naiyu; Zheng, Ting; Goossens, Nick; Vleugels, Jef; Zhang, Dongxing; Seveno, David
Abstract: Due to the inert carbon fiber (CF) surface and the poor wettability of CF with poly(ether ether ketone) (PEEK), the fiber-matrix interface bonding of CF/PEEK composite is relatively weak, which limits the mechanical performance of the composite. Herein, a complex sizing agent containing Ti3 C2 Tx MXene, carbon nanotube (CNT), and a dual compatibilizer of polyetherimide (PEI) was fabricated to graft on the CF surface. Compared with desized CF, the modified CF/PEEK composites showed a remarkable increase in flexural strength, flexural modulus, and interlaminar shear strength of 74.16%, 63.76%, and 62.79%, respectively. The improvement could be ascribed to the synergistic effects of multiple interactions, micromechanical interlockings, and substantially improved interfacial affinity by the hybrid grafting of MXene, CNT, and PEI. We also found that the interfacial failure mechanism changes from adhesive failure to cohesive failure with such a 1D/2D coating strategy. This facile and scalable approach demonstrates its potential for effectively improving fiber-matrix interfacial properties in CF/PEEK composites. Graphical abstract: Image 1 Highlights: A hierarchical structure containing 2D MXene, 1D CNT, and a dual compatibilizer of PEI was constructed on the CF surface. The tensile strength of modified CF showed an appreciable improvement of 12.02%. The ILSS (62.79%), flexural strength (74.16%), and flexural modulus (63.76%) of modified CF/PEEK composites were significantly enhanced.